Consistency of trematode infection prevalence in host populations across large spatial and temporal scales. Issue 7 (1st July 2016) - Byers, James E.; Holmes, Zachary C.; Blakeslee, April M. H.
Abstract: Parasites can impart heavy fitness costs on their hosts. Thus, understanding the spatial and temporal consistency in parasite pressure can elucidate the likeliness of parasites' role as agents of directional selection, as well as revealing variable environmental factors associated with infection risk. We examined spatiotemporal variation in digenetic trematode infection in 18 populations of an intertidal host snail ( Littorina littorea ) over a 300 km range at an 11‐yr interval, more than double the generation time of the snail. Despite a complete turnover in the snail host population, the average change in infection prevalence among populations was <1% over the 11‐yr span, and all but three populations remained within 5 percentage points. This consistency of prevalence in each population over time suggests remarkable spatiotemporal constancy in parasite delivery vectors in this system, notably gulls that serve as definitive hosts for the parasites. Thus, despite gulls' high mobility, their habitat usage patterns are ostensibly relatively fixed in space. Importantly, this spatiotemporal consistency also implies that sites where parasites are recruitment limited remain so over time, and likewise, that parasite hotspots stay hot.